IMPLEMENTASI TEORI ATRIBUSI UNTUK MENILAI PERILAKU KECURANGAN AKUNTANSI - Pasaribu, Ehud Mangaratua; Wijaya, Satria Yudhia (Fakultas Ekonomi dan Bisnis, Universitas Pembangunan Nasional Veteran Jakarta, 2017)
This study was conducted to examine the effect of internal control effectiveness, information asymmetry, and organizational commitment to the tendency of accounting fraud. This study uses the employees of the mining company's finance division as a sample. The technique of determining the sample using snowball method sampling method. The sample consisted of 50 respondents. Hypothesis testing in this study used Multiple Linear Regression Analysis with SPSS 21 program and 5% significance level. The results of the test show that (1) the effectiveness of internal control significantly influences the tendency of accounting fraud because it has a significance level of 0.002 smaller than the specified level α = 0.05. (2) information asymmetry has an effect and no significant to the tendency of accounting fraud because it has a significance level of 0.054 greater than the specified level α = 0.05, (3) organizational commitment has no effect and not significant to the tendency of accounting fraud because it has a level of significance Of 0.565 greater than the specified level α = 0.05.